Accessibility, Facilities And Digitalization Impact On Port Performance - Siti Maemunah; Destya Rahmayanti; Muhammad Iqbal Firdaus; Yuliantini Yuliantini; Mudjiardjo Mudjiardjo; Rully Indrawan (Dinasti Publisher, 2024)
The aim of this research is to determine the impact of accessibility, facilities and digitalization on port performance in Patimban Subang. Some of the main problems include; There is no direct access to the port, inadequate port support facilities such as the absence of a logistics company that has a home base in the port area means that goods delivery is not optimal. Apart from that, the use of the Inaportnet system as a form of port digitalization has not been optimal. This research method uses SEM-PLS analysis. The results of the analysis and discussion show that the variables of accessibility, facilities and digitalization of freight ports have a significant positive influence on port performance variables. The statistical test results show that all independent variables are statistically significant at the 95% confidence level, with a P-value lower than .